Gambaran Pengetahuan, Sikap dan Swamedikasi Pada Masyarakat Dilingkungan Pasar Merah Kelurahan Binjai - Rosanni S (Herbal Medicine Journal, 2021)
Self-medication or self-medication is a behavior to deal with minor illnesses before seeking help from an officer or health facility. More than 60% of community members do self-medication, and 80% of them rely on modern medicine. Indonesian medicine sources cover three interconnected sectors namely household medicine (self-medication), traditional medicine, and professional medical treatment. In Indonesia, residents who complained of pain during the last 1 month in 2004 were 24.41%. The treatment search efforts carried out by the people who complained of pain were mostly self-medication (87.37%). In this study aims to determine the knowledge of attitudes and actions of self-medication in the environment of 18 binjai red markets in Medan district. The number of samples to be tested is 97 by means of retrieval carried out descriptive research method, cross-sectional design using accidental sampling by processing spss data. The results of the study in general, the majority of respondents in choosing drugs were mostly limited use of over-the-counter drugs as many as 48 people (49.5%), the majority of respondents buying drugs in drug stores were 45 people (46.6%), the majority of fever complaints were 37 people (38.1% ), the reason for buying over-the-counter medicines mostly chose to save costs as many as 51 people (52.6%), the source of information was mostly from other people's recommendations, with respondents aged 30-40 as many as 39 people (40.2%), income 1,000,000-2,500,000 33 respondents (34.0%). In sufficient knowledge there were 53 people (54.6%). For self-medication actions in the environmental community 18 red markets, the binjai village received sufficient results, namely 50 people (51.5%). In general, the majority of respondents have sufficient attitudes towards self-medication, as many as 49 people (50.5%). Based on the results of this study, it is recommended that the health department to further improve health promotion, especially about self-medication so that public awareness can be further improved to carry out self-medication.